2013
DOI: 10.1080/01621424.2013.851048
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Psychosocial Variables for Home Care Services and How to Measure Them

Abstract: A Delphi-type expert consultation founded on the RAND/UCLA Appropriateness method was used to select variables related to older adults and environment characteristics perceived essential in assessing psychosocial needs and that could influence the social work workload in home care services. After two rounds of consultation, the 60 experts reached a consensus on 97 variables out of the 160 considered. A focus group made up of 10 experts identified tools that would allow us to measure the variables in a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…To our knowledge, this is the first study to demonstrate the benefits of equipping community care staff with social engagement and well-being instruments. While Delli-Colli, Dubuc, Hébert, Lestage, and Dubois (2013) found that identifying older adults' psychosocial needs can influence a social worker's decision to tailor services accordingly, adoption of psychosocial assessments has not yet been integrated into standard practice within community care. This is rather surprising given how social engagement and community participation is recognised as an indicator of successful ageing (Douglas, Georgiou, & Westbrook, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to demonstrate the benefits of equipping community care staff with social engagement and well-being instruments. While Delli-Colli, Dubuc, Hébert, Lestage, and Dubois (2013) found that identifying older adults' psychosocial needs can influence a social worker's decision to tailor services accordingly, adoption of psychosocial assessments has not yet been integrated into standard practice within community care. This is rather surprising given how social engagement and community participation is recognised as an indicator of successful ageing (Douglas, Georgiou, & Westbrook, 2016).…”
Section: Discussionmentioning
confidence: 99%